SPNS2 Downregulation Induces EMT and Promotes Colorectal Cancer Metastasis via Activating AKT Signaling Pathway - Lv, Lei; Yi, Qiyi; Yan, Ying; Chao, Fengmei; Li, Ming (Frontiers in Oncology, 2021)
Spinster homologue 2 (SPNS2), a transporter of S1P (sphingosine-1-phosphate), has been reported to mediate immune response, vascular development, and pathologic processes of diseases such as cancer via S1P signaling pathways. However, its biological functions and expression profile in colorectal cancer (CRC) is elusive. In this study, we disclosed that SPNS2 expression, which was regulated by copy number variation and DNA methylation of its promoter, was dramatically upregulated in colon adenoma and CRC compared to normal tissues. However, its expression was lower in CRC than in colon adenoma, and low expression of SPN2 correlated with advanced T/M/N stage and poor prognosis in CRC. Ectopic expression of SPNS2 inhibited cell proliferation, migration, epithelial–mesenchymal transition (EMT), invasion, and metastasis in CRC cell lines, while silencing SPNS2 had the opposite effects. Meanwhile, measuring the intracellular and extracellular level of S1P after overexpression of SPNS2 pinpointed a S1P-independent model of SPNS2. Mechanically, SPNS2 led to PTEN upregulation and inactivation of Akt. Moreover, AKT inhibitor (MK2206) abrogated SPNS2 knockdown-induced promoting effects on the migration and invasion, while AKT activator (SC79) reversed the repression of migration and invasion by SPNS2 overexpression in CRC cells, confirming the pivotal role of AKT for SPNS2’s function. Collectively, our study demonstrated the suppressor role of SPNS2 during CRC metastasis, providing new insights into the pathology and molecular mechanisms of CRC progression.